“Glocalisation” doctrine in the Israeli Public Education System: A contextual analysis of a policy-making process - Dvir, Yuval; Maxwell, Claire; Yemini, Miri (Education Policy Analysis Archives, 2019)
In 2016, the Israeli Ministry of Education (MoE) issued a policy document recommending six new doctrines for pedagogical development at schools. Amid those is ‘Glocalism’, aimed at addressing the global/local mix within the schooling system. Given the lack of a declared internationalization policy in Israel and its highly nationalistic curricula, this direction may constitute a first attempt by the MoE to internationalize school curricula. Public participation, including third-sector organizations actors, constituted a fundamental element in the development of this policy. Examining why this is, and what impact it had on how internationalization was conceived of is critical in this era of pluri-scalar policy-making. Our findings highlight the crucial role played by various non-governmental actors in this process. We also reveal that certain voices were in effect silenced – whether from marginalized constituencies or those suggesting directions contradicting the MoE’s intentions. The policy offers a vague definition for ‘Glocalism’, which appears to eliminate possibilities for marginalizing those communities who feel most challenged by this policy move. Yet, this open-endness in the conceptualization of internationalization is likely to further increase current inequalities within the education system. We argue that such public participation processes can therefore easily become pseudo-participatory, marginalizing and excluding particular constituents.